Navigation-Assisted Bone Grafting for Blowout Fracture. Issue 2 (March 2016) - Ogino, Akihiro; Onishi, Kiyoshi; Yamada, Tetsuo
Abstract : Background: Treatment of orbital floor fracture accompanied by extensive bone defect requires orbital floor reconstruction using a bone graft, but graft may deviate into the maxillary sinus when no bone capable of supporting the graft remains around the defect. In such cases, it is necessary to fix the grafted bone to the orbital margin, but the grafted bone placement site is subjectively decided based on inspection through a small incision in many cases, being dependent on the experience of operators, and it has been difficult to accurately determine the placement angle. Methods: The authors applied a navigation system in 4 patients with orbital blowout fracture, and evaluated for the exact bone graft placement angle and orbital floor form during surgery. Results: The bone graft placement angle was evaluated by comparison with a mirror image of the nonaffected side. The angle could be confirmed during surgery, as well as the lateral symmetry of the orbital form. On postoperative computed tomography, the grafted bone was retained at a favorable placement site. Conclusions: The navigation system may be useful to support the treatment of orbital blowout fracture, as it facilitates safe dissection around orbital floor bone defects, confirmation of the positional relationship between the bone fragment and orbital tissue and bone graft fixation position, and evaluation of lateral symmetry of the orbital floor form during surgery.